What is the general solution for (cosX + sinX)(1 - 2sinX)=0

Answers

Answer 1
Answer: 1. square both sides, a straight forward method. 
2. hand plot 
3. calculator plot, not recommended.Let Y=sin x + cos x -1 
Y=0, find x=? 
4. Substitute 1=sin^2(x) + cos^2(x) on the right hand side 
Y1=sin^2(x) - sin(x) 
Y2=cos^2(x) - cos(x) 
Y1 + Y2=0, Y1=0, Y2=0, 
a(a-1)=0, so, a=0, a=1, where a=sin(x), or cos(x), 
so x=0, pi/2 
Have a good day!

Related Questions

In which scenario would someone want to use the Paste Link option?A. Jimmy is writing an email to his friend. He wants to copy and paste a graph that he made in a spreadsheet into his email to show his friend. B. Joyce is writing a paper on global warming. She copied and pasted a chart that she found in an online journal into her paper. C. Jack is making a slide show of pictures from his last vacation. He has been reviewing his pictures and copying and pasting the best ones for the slide show. D. Jamie is continually entering data on poverty rates around the country into a spreadsheet. She copied and pasted key parts of her data into her paper.
If <8m 23 find the measure of each missing angle
the sum of two numbers is 13 2 times the first number minus 3x and the second number is 1 if you let X stand for the first number and why for the second number what are the two numbers
: Sergio wants to fence in a circular portion of his backyard for a play space for his dog. Determine the area of the largest portion of the yard he can enclose with 72 feet of fencing. Use 3.14 for π.
5a squared + 4ab I need help with my online homework

What is the value of y in the equation 4(5y –8 –2) = 185 –15?

Answers

In an equation the Left hand side must equal the right hand side 4(5y-8-2)=185-15 20y-32-8=170 20y=170+32+8 20y=210 Therefore y=10,5 When you substitute the 10,5 and solve it on the left and side it's equal to 170 which is the answer on the right hand side

Answer: 10.5

Step-by-step explanation:

I know this cause I'm smart lol

Help with this question? I got half of it, but can't seem to get the other half. Please explain how you got your answer. Thanks!1. The equation of a plane in space is x + 3y + 2z = 6.
a.) Accurately sketch the plane on the set of axes, showing all your calculations below.
b.) The three planes of the axes and the plane you have sketched create a triangular pyramid. Find the volume of this pyramid, showing the formula you are using and all
calculations below.

My Answer:
a. I started off by finding my x-intercept. To find my x-intercept I substituted y and z with 0. So: x + 3(0) + 2(0) = 6. After multiplying and adding, I end up with x = 6. So my x-intercept is (6, 0, 0,). T find my y-intercept I substituted x and z with 0. So: 0 + 3y + 2(0) = 6. After multiplying and adding, we come up with 3y = 6. Now we divide each side by 3 to get y = 2. So my y-intercept is (0, 2, 0). To find my z-intercept, I substituted x and y with 0. So, 0 + 3(0) + 2z = 6. After multiplying and adding, I get 2z = 6. Now I divide each side by 2 to get z = 3. So my z-intercpet is (0, 0, 3). After I plotted the points and connected them, they formed a triangular pyramid.

So thats how much i got. I cant seem to figure out how to get the volume. please help.

Answers

Answer:

Volume of the pyramid = 6 cubic units

Step-by-step explanation:

The volume of a triangular pyramid is: V = (1/3)*A*H

where A is the area of the triangle base, and H is the height of the pyramid.

Taking the triangle formed in the x-y plane as the base, its area is computed as follows:

A = (1/2)*6*2 = 6 square units

where 6 and 2 are the measure of the two perpendicular sides of the triangle.  This is taken from the x-intercept point  (6, 0, 0) and  y-intercept point  (0, 2, 0).

The height of the pyramid is then the measure of the z-intercept point (0, 0, 3), that is, 3. Replacing in volume formula:

V = (1/3)*A*H

V = (1/3)*6*3

V = 6 cubic units

X - Intercept
    x + 3y + 2z = 6
x + 3(0) + 2(0) = 6
        x + 0 + 0 = 6
              x + 0 = 6
                 - 0  - 0
                    x = 6
X - Intercept: (6, 0, 0)

Y - Intercept
  x + 3y + 2z = 6
0 + 3y + 2(0) = 6
    0 + 3y + 0 = 6
    0 + 0 + 3y = 6
          0 + 3y = 6
        - 0         - 0
                3y = 6
                 3     3
                  y = 2
Y - Intercept: (0, 2, 0)

Z - Intercept
x + 3y + 2z = 6
0 + 3(0)  2z = 6
  0 + 0 + 2z = 6
        0 + 2z = 6
      - 0         - 0
              2z = 6
               2     2
                z = 3
Z - Intercept: (0, 0, 3)

Volume of the X - Intercept, Y - Intercept, and Z - Intercept
V = ¹/₃(¹/₂lwh)
V = ¹/₃(¹/₂(6)(2)(3))
V = ¹/₃(¹/₂(12)(3))
V = ¹/₃(¹/₂(36))
V = ¹/₃(18)
V = 6 u³

Express the set in roster form.

{x|x is a natural number multiple of 5}

Answers

\{x|x\in\mathbb{N}\ and\ multiple\ of\ 5\}=\{0;\ 5;\ 10;\ 15;\ 20;...\}=5k\ (k\in\mathbb{N})

Round to the nears ten 9.42?​

Answers

Answer:

9

Step-by-step explanation:

In order to round to the nearest ten you must think: what is the nearest multiple of 10. For example, to round 68 to the nearest 10, the nearest whole number is 70, so the answer would be 70. However if you were to round 63 to the nearest 10, to would be 50 since that is the nearest multiple of 10

Answer:9

Step-by-step explanation:

Since the next number is below five you don’t round up it just stays the same

A 1400 sq ft house is advertised for sale at a price of $125,000. What is the cost per square foot?

Answers

The answer is $89.28.

Let's use the proportion for this:
If 1400 ft² costs $125,000, 1 ft² will cost x:
1400 ft² : $125,000 = 1 ft² : x

Now, crossing the products:
x · 1400 ft² = $125,000 · 1 ft²
· 1400 = $125,000
x = $125,000 
÷ 1400
x = $89.28

Therefore, 1 square foot costs $89.28.
If you would like to know the cost per square foot, you can calculate this using the following steps:

1400 sq ft house ... $125,000
1 sq ft ... $x = ?

1400 * x = 125,000 * 1
1400 * x = 125,000
x = 125,000 / 1400
x = $89.29

The correct result would be $89.29.

Isaiah determined that 5a^2 is the GCF of the polynomial a^3 - 25a^2b^5 - 35b^4. Is he correct? Explain

Answers

The answer is no, he did not arrive with the correct answer. With Isaiah claiming that 5a^2 is the GCF of the polynomial a^3 - 25a^2b^5 - 35b^4, he is incorrect because the constant '5' does not apply to the first factor of the equation which is 'a^3'. 

Answer:

No, Isiah is not correct. The GCF of the coefficients is 1, and there are no common variables among all three terms of the polynomial. 5b4 is a factor of -25a2b5 and -35b4, but not a3. Additionally, a2 is a factor of a3 and -25a2b5, but not -35b4.